Perancangan Kursi Antropometri Berbasis Sensor HC-SR04 - Arni Nazirah; Emon Azriadi; Resy Kumala Sari (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to design an antropometric chair using the QFD method aimed at identifying and meeting consumer needs and desires for the product or service produced. Anthropometric chair is specially designed for measuring the dimensions of the human body in a sitting position. This chair is designed to increase product accuracy and comfort, save time in thr measurement process and minimize product manufacturing errors due to errors in manual measurement. Anthropometric chair design based on consumer desires using the QFD (quality function deployment) method which has been processed using the house of quality, it can be seen that the percentage of the highest value or priority for product attributes is “a chair that accurately reads body dimensions” with a value presentation of 12,436% followed by “seat component can be unscrewed”with a value of 10,424%, then on the third priority,namaley “seats with appropriate and affordable prices” with a value of 10.147%. Anthropometric chair product design specifications based on voice of customer statements are that in the features section there are size sensors for measuring hand length, measuring arm span, measuring waist height, measuring leg height, and measuring height in sitting position. And for reliability, rubber is attached to the chair legs. Durability is not easily broken, portability the components of the anthropometric chair can be opened and paired, the aesthetics of the chair is given more attractive colors and designs and also the anthropometric chair can be used by anyone.